2017
DOI: 10.3390/nu9040403
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Ameliorates Ischemia/Reperfusion-Induced Renal Injury in a SIRT1-Dependent Manner

Abstract: Renal ischemia/reperfusion (I/R) injury continues to be a complicated situation in clinical practice. Genistein, the main isoflavone found in soy products, is known to possess a wide spectrum of biochemical and pharmacological activities. However, the protective effect of genistein on renal I/R injury has not been well investigated. In the current study, we explore whether genistein exhibits its renal-protective effects through SIRT1 (Sirtuin 1) in I/R-induced mice model. We found the treatment of genistein si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…SIRT1, a class III histone deacetylase whose activity is dependent on NAD + , regulates a wide array of cellular processes, including oxidative stress, metabolism, apoptosis, and aging by deacetylating both histone and nonhistone proteins [61]. SIRT1 plays a protective role against IR injury in the heart [61], kidney [62], brain [63], and liver [64]. Previous studies have demonstrated that SIRT1 deacetylates its downstream targets, including NF-κB, Foxos, p53, and peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), to regulate apoptosis, inflammation, and oxidative stress and protect organs from IR injury [65].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1, a class III histone deacetylase whose activity is dependent on NAD + , regulates a wide array of cellular processes, including oxidative stress, metabolism, apoptosis, and aging by deacetylating both histone and nonhistone proteins [61]. SIRT1 plays a protective role against IR injury in the heart [61], kidney [62], brain [63], and liver [64]. Previous studies have demonstrated that SIRT1 deacetylates its downstream targets, including NF-κB, Foxos, p53, and peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α), to regulate apoptosis, inflammation, and oxidative stress and protect organs from IR injury [65].…”
Section: Discussionmentioning
confidence: 99%
“…Ohwi and Sophora japonica L. Genistein is structurally similar to estrogen and has a number of biological properties that can prove benecial in alleviating a variety of health conditions including kidney disease, menopausal symptoms, neuronal loss, Alzheimer's disease, and cancer. [1][2][3][4][5][6][7] Because of this broad range of biological properties, genistein has gained attention as a food additive and dietary supplement. Currently, there is an enormous demand for genistein in health and food products.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Isoflavones supplementation failed to inhibit hyperglycaemia in KKAy mice, unlike in type 1 diabetes model, probably due to a pancreatic injury in this T2D model. Additionally, genistein reduced renal tubular cell death caused by ischemia/reperfusion injury [ 23 ] and cisplatin‐induced injury. [ 24 ] Furthermore, genistein attenuates epithelial–mesenchymal transition and inhibits profibrotic protein expression in renal tubular cells stimulated by parathyroid hormones.…”
Section: Discussionmentioning
confidence: 99%